Estação ecológica do Castanhão – Ce: análise geoecológica da paisagem e proposta de gestão ambiental - Sena, Liana Mara Mendes de (2011)
Protected areas are fundamental tools in any strategy for nature conservation. However, their creation is not only sufficient to effect protection. The Caatinga is the only exclusively Brazilian biome and has a rich biodiversity, high rates of endemism and a strong human pressure on natural resources. However, only 1% of the biome is protected by protected areas for full protection. This study was conducted at the Ecological Station of Castanhão (Brazilian category), created in 2001 as compensation for the environmental impacts generated by the construction of Castanhão dam, the largest in the state and the Northeast. Owns 12,579 ha in area and is located in the cities of Jaguaribara, Alto Santo and Iracema, in order to protect the samples Caatinga ecosystem, conduct scientific research and environmental education, and is administered by ICMBio. This research aimed to conduct the analysis geoecologic Landscape in Ecological Station of Castanhão, in order to contribute to the development of a draft environmental management plan and its implementation. And had the following objectives: to describe and analyze the geoecological units present at Ecological Station, performing integrated diagnosis identifying impacts, limitations and potential, and make proposals and guidelines for the viability and effectiveness of the environmental management of the Ecological Station. The methodological foundation was based on geoecology landscape, which has its premises in systems theory and the study of landscape. The techniques of cartography and GIS and field surveys enabled the achievement of results. Were delineated and characterized different ecology units, with relief as the main differentiating factor. The results showed as major impacts within the agriculture, extraction of vegetation, hunting and the presence of roads as factors limiting the conservation area. The state of conservation and land use showed that 36% of the area is used for agriculture, contains 18.2% and 15.7% conserved vegetation provides soil devoid of vegetation. From these data was elaborated proposed zoning unit, divided into intangible zone, buffer zone, special-use zone, recovery zone and buffer zone. Later, it was proposed mosaic of conservation with the establishment of new protected areas and wildlife corridors 2, highlighting the role of these areas for the recovery of degraded areas and the importance of the Ecological Station Castanhão in the regional context. The geoecology landscape proved an effective tool for the study of conservation and environmental planning.